2017
DOI: 10.14203/jet.v17.30-35
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Catalytic Material Effect on the Photovoltaic Properties of Monolithic Dye-sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSC) are widely developed due to their attractive appearance and simple fabrication processes. One of the challenges that arise in the DSSC fabrication involves high material cost associated with the cost of conductive substrate. DSSC with monolithic configuration was then developed on the basis of this motivation. In this contribution, titanium dioxide-based monolithic type DSSCs were fabricated on a single fluorine-doped transparent oxide coated glass using porous ZrO2 as spacer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…For the counter electrode material, carbon was preferred since it showed better performance compared to platinum when used in monolithic DSSC according to our previous report [21]. Carbon was directly applied on the photoelectrode side, partially right on the ZrO2 layer and the remaining layers were crossed over the other FTO area.…”
Section: Sample Composition Ratios El-hpe El-hsementioning
confidence: 99%
See 1 more Smart Citation
“…For the counter electrode material, carbon was preferred since it showed better performance compared to platinum when used in monolithic DSSC according to our previous report [21]. Carbon was directly applied on the photoelectrode side, partially right on the ZrO2 layer and the remaining layers were crossed over the other FTO area.…”
Section: Sample Composition Ratios El-hpe El-hsementioning
confidence: 99%
“…There are some factors that can be argued related to these results. First, the manual design of monolithic cells in planar architecture is likely considered as the cause of imperfect contact between the electrodes [21], which can contribute to charge recombination. The existence of spacer layer can also become the contributing factor for the low value possibly due to its inappropriate thickness, which potentially could promote recombination between the photogenerated electrons in semiconductor and holes in the electrolyte [23].…”
Section: Sample Composition Ratios El-hpe El-hsementioning
confidence: 99%
“…V OC values play a significant role in the process of charge injection in cells in the DSSC. Almost half the energy of photons lost in the cell due to dye regeneration [7]. In Table 3, the activated carbon has a higher V OC value compared to V OC carbon nanopowder.…”
Section: Measured Using Nitrogen Gas Sorption Techniquementioning
confidence: 99%
“…In addition, carbon also has corrosion-resistant properties and has good electro-catalytic ability [6]. Furthermore, our previous result showed that carbon produced better performance than sputtered platinum when applied as the counter electrode in monolithic DSSC [7]. In particular, carbon nanopowder and activated carbon will be compared.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the research on monolithic DSSC is still wide open to obtain optimal performance. The previous study reported that the thickness of both spacer and counterelectrode materials have significant effects on the performance of monolithic DSSC [11].…”
Section: Introductionmentioning
confidence: 99%